Near-field distributions and radiation patterns of hollow dielectric wall pyramidal horn antennas - Tiwari T.; Tiwari V.N. (My University, 2025)
Aperture/near-field distributions and radiation patterns of hollow dielectric wall pyramidal horn antennas have been studied theoretically and experimentally. Solution of the Helmholtz’s equation is obtained for the TE to x mode, using the separation of variables technique for the horn, assumed to be made of an equivalent homogeneous dielectric material of dielectric constant equal to the effective dielectric constant of the dielectric slabs and inner free space region bounded by these slabs. Transcendental equations for the transverse components of the propagation constants are obtained by applying proper boundary conditions, i.e. the continuity of the electric and magnetic fields at the dielectric–air boundaries. These transcendental equations are solved for the transverse propagation constants for the fundamental mode for the horn of axial length = 10.2cm, and of angles of flare in the H- and E-planes of 8.5° and 6.5°, respectively, at 9.418GHz in the X-band. The expressions for the near-field components of the horn under study are used to obtain the expression for radiation pattern from Kirchoff’s diffraction formula. The theoretical aperture field distributions obtained for the Hx11 mode propagating in the antenna and 11 radiation patterns are compared with corresponding experimental ones. © 1998 Taylor and Francis Group, LLC.